As filhas da Imaculada Conceição : um estudo sobre educação católica (1915 - 1970) - Melo, Valéria Alves (2008)
The present work discusses the Catholic feminine education in Sergipe, taking as base Our School Mrs. of the Tranks, founded in 1915, in the city of Propriá, for the congregation of Immaculate Conceição s Hospitable Franciscan Sisters, to instruct the girls of the area starting from the beginnings of the faith and of the Crhistean morals. Has as main objective to discuss the path of this teaching in the period from 1915 to 1970, for acting moments of the largent importance: the installation of the school and the adtion of milddle teaching. The mork examines the culture of catholic feminine education at pass 55 gears, with base in memory of the students and teachers that there studied, in archives of institution and of the Secretary of State of the Education, in Public Archive of State of the Sergipe and in periodical printing.